Gestational diabetes and endothelial function: impact of gestational insulin resistance on reactive hyperhemia index - Seck, Aissatou; Sall, Oumou M.; Agne, Fatou Diallo; Fall, Abibatou Sall; Samb, Abdoulaye; Ba, Abdoulaye (International Journal of Research in Medical Sciences, 2022)
Our aim was to characterize endothelial function in gestational diabetes by evaluating the reactive hyperemia index (RHI, LnRHI). A prospective, descriptive and comparative study was conducted on a population of pregnant women aged over 20 and under 36, located in the gestational age group 24-38th week of amenorrhea. They were divided into two groups. Group 1 (G1): group of pregnancies without diabetes, consists of pregnant women with no risk factor for gestational diabetes and with normal fasting blood glucose. Group 2 (G2): group of pregnancies with diabetes, includes pregnancies whose oral glucose tolerance tests (OGTT) came back positive. Anthropo-physiological parameters (age, weight, height, blood pressure (PA) and biochemical parameters (glycemia, insulinemia, HOMA-IR, cholesterol, triglycerides) were measured. RHI and LnRHI were determined at Endopat 2000. The two groups were matched for age, weight, heart rate (HR) and blood pressure (BP). Levels of glucose (G1:0.76±0.11; G2:1.11±0.11; p˂0.0001), insulin (G1:7.67±4.35; G2:22.9±3.75; p˂0.0001), HOMA-IR (G1:1.51±0.97; G2:6.29±1.23; p˂0.0001), total cholesterol (G1:1±0.81; G2:2.49±0.74; p=0.002), HDL cholesterol (G1:0.45±0.23; G2: 0.8±0.19; p=0.004, LDL cholesterol (G1:0.42±0.54; G2:1.39±0.6; p=0.004), triglycerides (G1:0.65±0.49; G2:1.48±0.27; p=0.0018), were significantly higher in the diabetic group. Both RHI and LnRHI were negatively correlated with HOMA-IR (respectively, r=-0.8931, p<0.0001; r=-0.8938; p<0.0001). HOMA-IR index was independently associated with levels of RHI and LnRHI (respectively r²=0.797; p<0.0001); (r²=0.804; p<0.0001)). Thus, gestational insulin resistance would be associated with a change in endothelial function such as a decrease in endothelium-dependent vasodilatation reflecting endothelial dysfunction, hence an increase in cardiovascular risk.